1998
DOI: 10.1254/jjp.76.313
|View full text |Cite
|
Sign up to set email alerts
|

Bifemelane Protects Cultured Cortical Neurons Against N-Methyl-D-aspartate Receptor-Mediated Glutamate Cytotoxicity

Abstract: This study was performed to examine the neuroprotective action of bifemelane against glutamate cytotoxicity in cultured cortical neurons obtained from fetal rats. Cell viability was markedly reduced by a brief exposure to glutamate. Glutamate cytotoxicity was reduced by exposing cultures to bifemelane at concentrations of 1-10 microM for 24 hr prior to glutamate exposure. In contrast, glutamate cytotoxicity was not affected by adding bifemelane to the glutamate-containing-medium without pretreatment. Bifemelan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…5). This range is similar to the nicotine concentration, from 1 to 100 M, found to be neuroprotective in studies with neuronal cultures (Akaike et al, 1994;Marin et al, 1994;Kihara et al, 1998Kihara et al, , 2001DajasBailador et al, 2000). Minana et al (1998) showed neuroprotection by 10 nM nicotine against glutamate and 10 M against NMDA.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…5). This range is similar to the nicotine concentration, from 1 to 100 M, found to be neuroprotective in studies with neuronal cultures (Akaike et al, 1994;Marin et al, 1994;Kihara et al, 1998Kihara et al, , 2001DajasBailador et al, 2000). Minana et al (1998) showed neuroprotection by 10 nM nicotine against glutamate and 10 M against NMDA.…”
Section: Discussionsupporting
confidence: 73%
“…Although nicotine and other nAChR agonists were shown to be neuroprotective in a variety of experimental systems, they were never studied in acute slices. Nicotine was found to be neuroprotective in neuronal cultures against glutamate, NMDA, and some of its analogs (Akaike et al, 1994;Marin et al, 1994). Nicotinic neuroprotective activity was reported to be dependent on active ␣7 nAChRs and Ca 2ϩ (Dajas-Bailador et al, 2000;Kihara et al, 2001).…”
mentioning
confidence: 99%
“…121 Taken together experimental and clinical data largely indicate a neuroprotective/trophic role of nAChR modulation involving mainly ␣4, ␤2-and ␣7-nAChR subtypes. 120,[122][123][124][125][126][127][128] While it is clear that some level of nAChR activation is required for these neuroprotective/trophic effects to occur, it is also clear that overstimulation of certain nAChR subunits, such as ␣7 can lead to cytotoxicity. 129,130 In fact, many of the neuroprotective nAChR ligands, including nicotine, have been characterized as partial agonists allowing for only a percentage of the current that would be achieved by full ACh-induced nAChR activation.…”
Section: Limitationsmentioning
confidence: 99%
“…Nicotine protects against the degeneration of dopamine neurons in animal models of Parkinson's disease or after high doses of METH (Maggio et al, 1998;Costa et al, 2001;Ryan et al, 2001;Parain et al, 2003) through its ability to modulate NMDA receptor function (Rao et al, 1997) and protect against NMDA-mediated excitotoxicity that may occur due to increases in striatal glutamate after METH (Nash and Yamamoto, 1992). In fact, in vitro studies suggest that ␣7 nicotinic receptor modulation is protective against NMDA-mediated excitotoxicity to PC12 cells and hippocampal cultures (Akaike et al, 1994;Carlson et al, 1998;Prendergast et al, 2001). Conversely, the protective effect of nicotine is absent in ␣7 NAchR knockout mice (Gahring et al, 2003).…”
Section: Lobeline Effects On Methamphetamine Toxicity 165mentioning
confidence: 99%